How Digitization and Data Analytics Transform Auditing and Society - Aynura HAJIYEVA; Nazaket MUSAYEVA; Mehriban ALIYEVA; Gular AKBAROVA (Communications of International Proceedings, 2021)
The main purpose of this publication is the research and study of the digital economy, as this point remains the important issue of integration into the business models based on digital platforms. The world as we know is constantly changing and digital transformation is one of the main drivers. So what is the digital economy? It is an economic activity that results from billions of daily online connections between people, businesses, devices, data and processes. The backbone of the digital economy is hyper-connectivity, which means the growing interconnection of people, organizations and machines, which is the result of the Internet, mobile technology and the Internet of Things. Nowadays, has been formed completely new "information value chain" in the economy world, consisting of firms that support the collection, storage, analysis and modeling of information. In this case, the creation of value occurs in the conversion of information into money through digital intelligence and commercial use. The digital economy is taking shape and undermining traditional business structure; how firms interact; and how consumers receive services, information and goods. TechCrunch, the digital economy news site recently noted, “Uber, the world's largest taxi company, has no vehicles. Facebook, the world's most popular media owner, doesn't create any content. Alibaba, the most expensive retailer, has no inventory or the world's largest housing company, doesn't own real estate. We want research what is so special about these companies that allows them to rethink the traditional boundaries and value propositions of their industry.
Keywords: Digital Platforms; Blockchain Technology; Robotic Process Automation; Digital Economy